Production of green diesel via cleaner catalytic deoxygenation of Jatropha curcas oil - Mijan, Nurul Asikin; Lee, Hwei V.; Alsultan, G. Abdulkareem; Afandi, Aflah; Taufiq-Yap, Yun Hin (Elsevier, 2018)
Utilization of green diesel derived from biomass in industries and transportation has significantly increased energy security by reducing the dependency on the petroleum and balancing the overall greenhouse gas emission. In the present study, jatropha oil-derived green diesel was produced via catalytic deoxygenation process by using multi-walled carbon nanotube (MWCNTs)-supported catalysts (Co/MWCNT, Ni/MWCNT and Ni–Co/MWCNT). The use of active bimetallic promoter (Ni–Co) showed high catalytic activity in decarboxylation/decarbonylation routes with a total of 80% of saturated and unsaturated hydrocarbon in range of C8–C17. Furthermore, Ni–Co/MWCNT showed high selectivity towards C15- and C17-hydrocarbon, which suggested that the presence of acidity work selectively in mild cracking of triglyceride structure and performed actively in deoxygenation.